Analisis Regresi Robust Estimasi Least Trimmed Square dan Estimasi Maximum Likelihood pada Pemodelan IPM di Pulau Sulawesi - Ingka Rizkyani Akolo; Asriyati Nadjamuddin (Universitas Negeri Gorontalo, 2022)
Sulawesi Island is one of the islands in Indonesia with the second lowest HDI after Papua in 2011-2018, so it is necessary to study more deeply the factors that affect the HDI on Sulawesi Island. One of the methods in modeling is the robust regression method that can be used even though there are outliers in the data. This study aimed to determine the factors that affect HDI in Sulawesi Island using a robust regression model of Least Trimmed Square (LTS) estimation and Maximum Likelihood (M) estimation and to find out the best method for modeling HDI in Sulawesi Island. The robust regression of the LTS estimate has a reasonably high breakdown point value compared to other estimates, while the M-estimate has a high efficiency. The results showed that the factors that affect HDI on the island of Sulawesi are Life Expectancy (UHH), Expected Years of Schooling (HLS), Average Years of Schooling (RLS), and Real Expenditures per capita (PPP). The best model in HDI modeling in Sulawesi Island is a robust regression model with LTS estimation where the standard error is 0.1513, and the R-Square is 99.78%. A very high R-Square value indicates that the ability of the UHH, HLS, RLS, and PPP variables to explain HDI is very good.